2022
DOI: 10.1002/smll.202204153
|View full text |Cite
|
Sign up to set email alerts
|

A Precipitation‐Enhanced Emission (PEE) Strategy for Increasing the Brightness and Reducing the Liver Retention of NIR‐II Fluorophores

Abstract: The lack of organic fluorophores with high quantum yields (QYs) and low liver retention in the second near‐infrared (NIR‐II) window has become a bottleneck in the bioimaging field. An approach to address these problems is proposed by encapsulating phosphorylated fluorescent dyes into biodegradable calcium phosphate nanoparticles. First, an NIR‐II molecule, LJ‐2P, is designed with increased water solubility by introducing two phosphate groups. Meanwhile, LJ‐2P co‐precipitates with calcium ions to form LJ‐2P nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…2-Bromo-9,9-dimethyl-9 H -fluorene and 4,4,4′,4′,5,5,5′,5′-octamethyl-2,2′-bi­(1,3,2-dioxaborolane) were purchased from Bidepharm. 4,7-Bis­(7-bromo-2,3-dihydrothieno­[3,4- b ]­[1,4]­dioxin-5-yl)-5,6-dinitrobenzo­[ c ]­[1,2,5]­thiadiazole was synthesized according to our previous work . PLA (202H) was obtained from Daigang.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2-Bromo-9,9-dimethyl-9 H -fluorene and 4,4,4′,4′,5,5,5′,5′-octamethyl-2,2′-bi­(1,3,2-dioxaborolane) were purchased from Bidepharm. 4,7-Bis­(7-bromo-2,3-dihydrothieno­[3,4- b ]­[1,4]­dioxin-5-yl)-5,6-dinitrobenzo­[ c ]­[1,2,5]­thiadiazole was synthesized according to our previous work . PLA (202H) was obtained from Daigang.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous research, we reported a new type of NIR-II fluorescent dye with high quantum yield (QY) and low liver retention based on the precipitation-enhanced emission (PEE) effect. 43 In this study, another high brightness and stability NIR-II molecule, LJ-858, was synthesized and coprecipitated with a poly(D,L-lactic acid) (PLA) polymer to form LJ-858 nanoparticles (NPs). The CXCR2-modified MSCs were efficiently labeled with LJ-858 NPs without affecting their cell viability.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation